THE EFFECT OF AUTHENTIC MATERIALS ON EFL STUDENT’S VOCABULARY ACHIEVEMENTS - Dewi Fahriah Akib (Publikasi dan UKI Press UKI Toraja., 2020)
This study aims to know the effect of authentic materials on EFL student’s vocabulary achievements. The study employed Quasi-experimental design. The population consists of 90 students and the sample are 20 students taken from the fourth semester the department of English Education Bosowa University. The data were collected by administering a filling in the blank test with consisting of 40 questions using inferential statistics. The p-Value of posttest is lower than ? (0,00<0,05) The result indicates that the alternative hypothesis(H1) is accepted and of course the null hypothesis (H?) is rejected, it shows that using authentic materials has effect on EFL students’ vocabulary achievements used article of The Jakarta post Newspaper as teaching tools in the classroom.